2005
DOI: 10.1007/s11099-005-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

How to correctly determine the different chlorophyll fluorescence parameters and the chlorophyll fluorescence decrease ratio R<sub>Fd</sub> of leaves with the PAM fluorometer

Abstract: This contribution is a practical guide to the measurement of the different chlorophyll (Chl) fluorescence parameters and gives examples of their development under high-irradiance stress. From the Chl fluorescence induction kinetics upon irradiation of dark-adapted leaves, measured with the PAM fluorometer, various Chl fluorescence parameters, ratios, and quenching coefficients can be determined, which provide information on the functionality of the photosystem 2 (PS2) and the photosynthetic apparatus. These ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
303
2
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(338 citation statements)
references
References 36 publications
17
303
2
16
Order By: Relevance
“…It has been found that prolonged exposure to lead (Pb) leads to an additional decrease of F v /F m in Flavoparmelia caperata (Garty 2002). In our study, we also employed a fl uorescence decrease ratio (R Fd ), a parameter which, when measured at saturation irradiance is directly correlated to the net CO 2 assimilation rate (Lichtenthaler et al 2005). The R Fd values in control lichens were mostly similar to R Fd values found in lichen Anaptychia ciliaris (Valladares et al 1995).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been found that prolonged exposure to lead (Pb) leads to an additional decrease of F v /F m in Flavoparmelia caperata (Garty 2002). In our study, we also employed a fl uorescence decrease ratio (R Fd ), a parameter which, when measured at saturation irradiance is directly correlated to the net CO 2 assimilation rate (Lichtenthaler et al 2005). The R Fd values in control lichens were mostly similar to R Fd values found in lichen Anaptychia ciliaris (Valladares et al 1995).…”
Section: Discussionsupporting
confidence: 53%
“…Maximum quantum yield of PSII (F v /F m ), a widely used indicator of photosynthetic effi ciency of photosystem II, was calculated as (F m -F 0 )/F m (Maxwell and Johnson 2000). Additionally, the fl uorescence decrease ratio (R Fd ), a parameter directly related to the rate of photosynthesis (Lichtenthaler et al 2005), was calculated as (F m -F s )/F s , according to Lichtenthaler et al (2005).…”
Section: Chlorophyll Fl Uorescence Parametersmentioning
confidence: 99%
“…4b), similar to recovery responses of C0 2 assimilation and F v /F m in leaves of grapevine (Vitis vinifera L.) that were exposed to full sunlight following growth in the greenhouse under low UV irradiance and PAR (Kolb et al, 2001). Decreased F v /F m ratios recorded at the adaxial leaf side indicate photoinhibition occurring predominantly in the upper chloroplast layers (Lichtenthaler et al, 2005), which might be partly responsible for the differences between the response of F w IF m and A max . Calculated q/c a ratios indicated that the decrease in A max did not result from increased stomatal limitation of C0 2 uptake.…”
Section: Discussionmentioning
confidence: 53%
“…Photosystem II antenna trapping efficiency was calculated as F v 0 /F m 0 . The chlorophyll fluorescence decrease ratio (vitality index) was calculated in accordance with Lichtenthaler et al (2004) as…”
Section: Analysis Of Photosynthetic Acclimation To Coldmentioning
confidence: 99%